Preliminary study of the 270 Bloom Fricke xylenol gel phantom performance for 3D conformal radiotherapy using multiple radiation fields - Cavinato, Christianne C.; Souza, Benedito H.; Jr., Henrique Carrete; Daros, Kellen A. C.; Medeiros, Reginaa B.; Giordani, Adelmo J.; Campos, Letícia L. (Revista Brasileira de Física Médica, 2015)
The complex cancer treatment techniques require rigorous quality control (QC). The Fricke xylenol gel (FXG) dosimeter has been studied to be applied as a three-dimensional (3D) dosimeter since it is possible to produce 3D FXG phantoms of various shapes and sizes. In this preliminary study, the performance of the FXG spherical phantom developed at IPEN, prepared using 270 Bloom gelatin from porcine skin made in Brazil, was evaluated using magnetic resonance imaging (MRI) technique, aiming to use this phantom to 3D conformal radiotherapy (3DCRT) with multiple radiation fields and clinical photon beams. The obtained results indicate that for all magnetic resonance (MR) images of the FXG phantom irradiated with 6 MV clinical photon beam can be observed clearly the target volume and, in the case of coronal image, can also be observed the radiation beam projection and the overlap of different radiation fields used. The Fricke xylenol gel phantom presented satisfactory results for 3DCRT and clinical photon beams in this preliminary study. These results encourage the additional tests using complex treatment techniques and indicate the viability of applying the